Hypoxia and P. gingivalis Synergistically Induce HIF-1 and NF-κB Activation in PDL Cells and Periodontal Diseases. (15th March 2015) - Gölz, L.; Memmert, S.; Rath-Deschner, B.; Jäger, A.; Appel, T.; Baumgarten, G.; Götz, W.; Frede, S.
Abstract : Periodontitis is characterized by deep periodontal pockets favoring the proliferation of anaerobic bacteria like Porphyromonas gingivalis ( P. gingivalis ), a periodontal pathogen frequently observed in patients suffering from periodontal inflammation. Therefore, the aim of the present study was to investigate the signaling pathways activated by lipopolysaccharide (LPS) of P. gingivalis (LPS-PG) and hypoxia in periodontal ligament (PDL) cells. The relevant transcription factors nuclear factor-kappa B (NF- κ B) and hypoxia inducible factor-1 (HIF-1) were determined. In addition, we analyzed the expression of interleukin- (IL-) 1 β, matrix metalloproteinase-1 (MMP-1), and vascular endothelial growth factor (VEGF) in PDL cells on mRNA and protein level. This was accomplished by immunohistochemistry of healthy and inflamed periodontal tissues. We detected time-dependent additive effects of LPS-PG and hypoxia on NF- κ B and HIF-1 α activation in PDL cells followed by an upregulation of IL-1 β, MMP-1, and VEGF expression. Immunohistochemistry performed on tissue samples of gingivitis and periodontitis displayed an increase of NF- κ B, HIF-1, and VEGF immunoreactivity in accordance with disease progression validating the importance of the in vitro results. To conclude, the present study underlines the significance of NF- κ B and HIF-1 α and their target genes VEGF, IL-1 β, and MMP-1 in P. gingivalis and hypoxia induced periodontal inflammatory processes.